2015
DOI: 10.1103/physrevd.92.044003
|View full text |Cite
|
Sign up to set email alerts
|

Quasilocal rotating conformal Killing horizons

Abstract: The formulation of quasi-local conformal Killling horizons(CKH) is extended to include rotation. This necessitates that the horizon be foliated by 2-spheres which may be distorted. Matter degrees of freedom which fall through the horizon is taken to be a real scalar field. We show that these rotating CKHs also admit a first law in differential form.Comment: 15 pages. sequel to arXiv:1412.5115. Definition slightly modified, an appendix adde

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 55 publications
0
27
1
Order By: Relevance
“…Let us point out a key difference between this result and the results of earlier studies (Weiland et al 1978;Flå et al 1989;Ehsan et al 2009;Chatterjee & Misra 2015;Misra et al 2017;Chaudhuri & Roy Chowdh (2018)), which considered the effect of nonlinear Landau damping on an isolated soliton. Those earlier studies found that such a soliton will experience decay and a frequency shift of the carries.…”
Section: Summary and Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Let us point out a key difference between this result and the results of earlier studies (Weiland et al 1978;Flå et al 1989;Ehsan et al 2009;Chatterjee & Misra 2015;Misra et al 2017;Chaudhuri & Roy Chowdh (2018)), which considered the effect of nonlinear Landau damping on an isolated soliton. Those earlier studies found that such a soliton will experience decay and a frequency shift of the carries.…”
Section: Summary and Discussioncontrasting
confidence: 68%
“…has been derived for other types of plasmas; see, e.g.,Ehsan et al (2009);Chatterjee & Misra (2015);Misra et al (2017);Chaudhuri & Roy Chowdhury (2018); to name just a few studies. Related plasma models that also account for nonlinear Landau damping can be found, e.g., inMeiss & Morrison (1983); RoyChowdhury et al (1988); Flå et al…”
mentioning
confidence: 99%
“…Many of the more well-known aspects of Landau damping can be studied even for an infinite plane wave. Generalizing this setup to the more realistic case of propagating wave packet, the effects of group velocity resonances enter the picture [8][9][10]. In this context, the nonlinear theory of Landau damping due to group velocity resonance of wave envelopes has been developed in both classical [9] and semiclassical plasmas [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of e-p pair plasmas demonstrated that electrostatic solitary waves can be generated [40], though a Maxwellian distribution was assumed. A number of papers have also been devoted to the linear and nonlinear dynamics of electronacoustic waves [46,47], electrostatic waves [48][49][50][51][52][53][54][55], and in the presence of suprathermal (and non-thermal) electrons [46,50,52] in e-p pair plasmas. Moreover, the propagation of ion-acoustic waves [56][57][58][59], and dust-acoustic waves [60][61][62] have recently been studied in e-p plasmas.…”
Section: Introductionmentioning
confidence: 99%